Biological Evidence for the Benefit of Green Tea and EGCG in Arthritis - Ahmed, Salahuddin (Current Rheumatology Reviews, 2009)
The use of complimentary and alternative medicine (CAM) approaches is becoming increasingly popular among patients with rheumatoid arthritis (RA) and osteoarthritis (OA). Arthritis is a leading cause of work-related disabilities affecting approximately 1.0% of the United States population. The lack of adequate response combined with increased risk of adverse events to conventional therapy in RA or OA patients has prompted interest in evaluating CAM options for arthritis. In this regard, the last decade has shown a growing popularity of green tea (GT) in the management of arthritis. Researchers are studying GT and its constituents to provide scientific rationale for its benefit in arthritis. This review summarizes the disease pathogenesis and novel therapeutic targets for the treatment of arthritis. I also tried to address the current treatment options that are available as well as their limitations. Finally, this article reviews the emerging role of GT and its polyphenol, epigallocatechin-3-gallate (EGCG), in arthritis. Although the recent findings provide scientific evidence of the efficacy of GT or EGCG in several in vitro and in vivo models of arthritis, further preclinical studies to validate its safety profile and additional phase-clinical trials in RA patients are warranted to authenticate its beneficial effect in arthritis and possibly other rheumatic conditions.
Keywords: Green tea